TINDAKAN PENGHINAAN SEBAGAI ALASAN PEMAKZULAN WAKIL PRESIDEN TERPILIH PERSPEKTIF UUD 1945 DAN FIQH SIYASAH: Indikasi Atas Kepemilikan Akun Fufufafa Di Kaskus - Asrudi, Asrudi; Rosalima, Fahrica (al-Rasῑkh: Jurnal Hukum Islam, 2024)
One of the features of the presidential system is the process of presidential impeachment. The impeachment of the president is determined by a majority vote in the People's Consultative Assembly (MPR) proposed by members of the People's Representative Council (DPR) who have previously been tested in the Constitutional Court (MK) with reference to Article 7A of the 1945 Constitution as the reason for the impeachment of the President and/or Vice President. On the other hand, the elected Vice President for 2024 is indicated to have insulted several people over the ownership of the Fufufafa account on Kaskus. Therefore, this paper will explain how the impeachment process is carried out against the elected Vice President from the perspective of the 1945 Constitution and Fiqh Siyasah. The research method used in this paper is the literature study method. From the analysis conducted by the author, the process of impeaching the elected Vice President can be carried out if it is proven that they own the Fufufafa account based on the 1945 Constitution and Fiqh Siyasah. Thus, the results of this research can also help enhance understanding and knowledge about the mechanism of impeachment against the elected Vice President if proven to violate the provisions from the perspective of the 1945 Constitution and Fiqh Siyasah.